Bacteria: A Very Short Introduction - Amyes, Sebastian G. B. (New York Oxford University Press, 2013)
Aimed at biological science and medical students looking for an introduction to bacteria, as well as general readers who are simply intrigued by the topic. Bacteria form a fundamental branch of life. They are the oldest forms of life as we know it, and they are still the most prolific living organisms. They inhabit every part of the Earth's surface, its ocean depths, and even terrains such as boiling hot springs. They are most familiar as agents of disease, but benign bacteria are critical to the recycling of elements and all ecology, as well as to human health. In this Very Short Introduction, Sebastian Amyes explores the nature of bacteria, their origin and evolution, bacteria in the environment, and bacteria and disease. In looking at our efforts to manage co-evolving bacteria, he also considers the challenges of resistance to antibiotics. ABOUT THE SERIES: The Very Short Introductions series from Oxford University Press contains hundreds of titles in almost every subject area. These pocket-sized books are the perfect way to get ahead in a new subject quickly. Our expert authors combine facts, analysis, perspective, new ideas, and enthusiasm to make interesting and challenging topics highly readable
Includes Index and Illustrations.
Keywords: Bacteria